Some new Imitations of achilles tatius In the ? RecensIon of the Alexander romance - Stephen M. Trzaskoma (Exemplaria Classica, 2014)
This note explores further the connections between achilles tatius’ leucippe and clitophon and the ? recension of the alexander Romance noted earlier by Jouanno, adds several examples of verbal imitation, and suggests emending ???’ ?? ???? ?????? ????? ?? ????? at ? 28.1 to ???’ ??? ??????? ????? ?? ????? on the basis of the model of the novelistic hypotext.